Misliti skozi razpor - Stephanides, Stephanos (Primerjalna književnost, 2006)
As both a poet and an academic, in this essay I attempt a personal and academic exploration of the controversial and symbiotic relationship between philosophy and poetry. I make reference to several thinkers in the tradition of continental theory, from Nietzsche to Alphonso Lingis, and use the example of a poem by Derek Walcott. The argument raises questions about the ontology of language and what is at stake in the notion of truth when we consider Heidegger's translation of the Greek word for truth (aletheia) as "unforgetting." I hope to raise questions regarding how the conceptualizing faculty may (or may not) enhance our understanding of poetry and art.
Keywords: književnost; literature; literarna teorija; literary theory; mišljenje; poezija